2006
DOI: 10.1161/01.hyp.0000235681.25685.cf
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Impairs Bone Marrow–Derived Progenitor Cell Formation

Abstract: Abstract-Aldosterone has been suggested recently to cause vascular injury by directly acting on the vasculature, in addition to causing injury by raising the blood pressure. Bone marrow-derived endothelial progenitor cells (EPCs) have been shown to exert an important role in the repair of the endothelium. In addition, cell-based therapy using EPCs is emerging as a novel therapeutic strategy for myocardial and peripheral vascular diseases. However, impaired formation and function of EPCs has been observed in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 37 publications
5
40
1
1
Order By: Relevance
“…We then demonstrated that the exogenous supplementation of BH 4 markedly increased the eNOS dimerization and the NO generation, as well as improved in vivo endothelial repair capacity of early EPCs from PHAs, indicating that BH 4 treatment has beneficial effect on modifying hyperaldosteronemia-caused functional impairment of early EPCs. The MR that mediated the response to aldosterone expressing in early EPCs has been proved previously 15,16 and was identified in the present study again ( Figure S10). Spironolactone, a MR antagonist, has been generally applied in clinic for treatment with PHAs or the condition of secondary activation of renin-angiotensin-aldosterone system such as heart failure and myocardial infarction.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We then demonstrated that the exogenous supplementation of BH 4 markedly increased the eNOS dimerization and the NO generation, as well as improved in vivo endothelial repair capacity of early EPCs from PHAs, indicating that BH 4 treatment has beneficial effect on modifying hyperaldosteronemia-caused functional impairment of early EPCs. The MR that mediated the response to aldosterone expressing in early EPCs has been proved previously 15,16 and was identified in the present study again ( Figure S10). Spironolactone, a MR antagonist, has been generally applied in clinic for treatment with PHAs or the condition of secondary activation of renin-angiotensin-aldosterone system such as heart failure and myocardial infarction.…”
Section: Discussionsupporting
confidence: 84%
“…26 Previous studies reported that aldosterone treatment in vitro induced ROS production of early EPCs. 15,16 In the present study, we observed that the intracellular ROS and superoxide production were obviously increased in early EPCs from PHAs, which further proved that the high level of aldosterone induced oxidative stress of early EPCs in vivo. In endothelial cells, aldosterone-induced oxidative stress increases oxidative degradation of BH 4 that leads to eNOS uncoupling and subsequently decreased NO generation.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Renal tissue was immediately snap-frozen in liquid nitrogen and stored at Ϫ70°C and further processed according to a previously described method (6,13). After determination of the protein concentrations of the lysates with a protein assay kit (Bio-Rad, Richmond, CA), equal amounts of protein (100 g) were immunoblotted with rabbit anti-acetyl histone H3 (Lys9) polyclonal antibody (Upstate Biotechnology), HDAC1 (Sigma), HDAC2 (Santa Cruz Biotechnology), HDAC7 (Sigma), or ␣-SMA (Dako) and analyzed using standard SDS-PAGE and Western blotting (22). For the detection of HDAC1, the nuclear protein was used to reduce nonspecific bands observed in blots using the whole tissue extract.…”
Section: Methodsmentioning
confidence: 99%
“…After determination of the protein concentration of the lysates with a protein assay kit (Biorad, Richmond, CA), equal amounts of protein (10 g) were immunoblotted with rabbit anti-acetyl histone H3 (Lys9) polyclonal antibody (Upstate Biotechnology; dilution 1:10000) and analyzed by standard SDS-PAGE and Western blot analysis according to a previously described method. 40 Values obtained by densitometric analysis of Western blots for acetylated histone were normalized to those for actin and expressed as relative values to those of control. To measure the nuclear HDAC5 protein levels, NRK52E cells were washed with ice-cold phosphate buffer saline, and the nuclear protein was extracted using the Nuclear/Cytosol Fraction Kit (BioVision Research Products, Mountain View, CA) in accordance with the manufacturer's instructions.…”
Section: Western Blottingmentioning
confidence: 99%